Organic fertiliser and the use of mulch in cowpea production under semiarid conditions (Revista Ciência Agronômica, 2015)
The reduction on crop production observed in semiarid conditions is closely linked to soils degradationin their physical, microbiological and fertility aspects. Based on this premise, the effects of different types of organicfertilizers associated to the use of mulching in the production of cowpea grown in Paraíba state, Brazil, under semiaridconditions, was studied. The research was conducted under field conditions in the municipality of Casserengue, PB,from April to July 2010. The statistical design in randomized block design with five treatments and five replicates wasused, totaling 25 experimental units. Treatments consisted on application of cattle manure or biofertilizer on presenceor absence of mulch, plus a control treatment, without fertilization or mulching. It was found that cowpea plants grownunder the interaction between manure and mulch had higher phytomass and grain production.